2020
DOI: 10.1007/s10841-020-00279-3
|View full text |Cite
|
Sign up to set email alerts
|

Higher richness and abundance of flower-visiting insects close to natural vegetation provide contrasting effects on mustard yields

Abstract: The conservation of pollinating insects in agriculture is a global concern since the diversity of such organisms may affect the productivity of pollination-dependent crops. In this study, we assessed (i) how distances from natural vegetation affect the diversity (guilds, richness, abundance) of flower-visiting insects within mustard crops in Nepal, (ii) how insect richness and abundance are related to mustard yields (weight of seeds) and (iii) the contribution of flower-visiting insects to mustard pollination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The presence of butterflies on plantations could be caused by the attraction of several plant species in plantations that have the potential as a food source [11]. The natural habitats around plantations also could provide key resources to butterflies, such as perennial forage areas, nesting substrates, or breeding sites [12]. Based on articles that truly focused on flowervisiting insects, not only pollinators, our results showed that flower-visiting insects mostly belong to Hymenoptera.…”
Section: Discussionmentioning
confidence: 78%
“…The presence of butterflies on plantations could be caused by the attraction of several plant species in plantations that have the potential as a food source [11]. The natural habitats around plantations also could provide key resources to butterflies, such as perennial forage areas, nesting substrates, or breeding sites [12]. Based on articles that truly focused on flowervisiting insects, not only pollinators, our results showed that flower-visiting insects mostly belong to Hymenoptera.…”
Section: Discussionmentioning
confidence: 78%
“…Some of the crops included in this review, such as B. rapa and S. alba, have also been used as insectary plants [176]. Proximity to natural habitats with natural vegetation and where wild bees can locate their nests can also enhance the abundance of wild bees [104,115,128]. The flowers of crucifer crops can also temporarily benefit wild bees because of the food resource boost [129].…”
Section: Discussion and Main Conclusionmentioning
confidence: 99%
“…Other studies similar to this have shown that GLY treatment on weeds can have non-targeted negative effects on the richness and diversity of insects within a short or long time (Sharma et al, 2018), causing insect death, alteration in reproduction rates, and population size of numerous insect taxonomic group, including Hymenoptera, Coleoptera, and Orthoptera (Lins et al, 2007). In this study, results showed that GLY reduced insect diversity, which could negatively impact the ecological services as the productivity of > 88% of flowering plant species depend on diverse pollinators for sexual reproduction (Devkota et al, 2020). It can, therefore, be claimed that DUL can support insect diversity and richness and preserve a healthy ecosystem, while it ensures plant fertilization and maximizes plant genetic diversity (Siregar et al,2016).…”
Section: Insect Diversity and Richnessmentioning
confidence: 73%